PERENCANAAN STRATEGIK OPTIMALISASI DANA JURUSAN DESAIN DAN PRODUKSI BUSANA (DPB) SMKN 4 PENAJAM PASER UTARA - Basuki, Anita Dwi; Santosa, Agus; Indriawati, Prita; Haryaka, Usfandi; Masruhim, Muh. Amir (Prodi Pendidikan Ekonomi Universitas Balikpapan, 2026)
Vocational education plays a strategic role in preparing competent and job-ready graduates; however, the relatively high unemployment rate among vocational high school graduates indicates a gap between graduate competencies and industry needs. One effort to improve learning quality is through effective and strategic financial management. This study aims to analyze strategic planning in optimizing financial resources in the Fashion Design and Production Department (DPB) at SMKN 4 Penajam Paser Utara. This research employed a qualitative approach with a descriptive design. The research subjects were selected through purposive sampling, involving the principal, vice principal, head of department, treasurer, and productive teachers. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with data validity ensured through triangulation. The findings reveal that financial optimization is achieved through the implementation of strategic management, including needs-based planning aligned with learning outcomes, systematic team organization, implementation through production-based learning and the development of Teaching Factory (TEFA), and periodic evaluation. The study implies that adaptive and innovative strategies can enhance the effectiveness of financial management and support departmental independence in delivering industry-oriented learning.